Observation of Posttonsillectomy Wounds Using Endoscopy and Examination of the Postoperative Course by Wound Type - Yoshida, Akinori; Furukawa, Takatoshi; Nagase, Teruaki (International Journal of Practical Otolaryngology, 2022)
Palatine tonsillectomy is a surgical procedure that novice otolaryngologists should master early and is taught at many medical institutions. Unfortunately, however, the transoral procedure cannot provide a large enough field of view to doctors other than the one performing the operation. Therefore, it is difficult to share the surgical field and provide real-time teaching. Dissection of the wrong layer can cause postoperative bleeding and pain. Our department uses a 70-degree, 4-mm rigid endoscope for palatine tonsillectomy, which makes it possible for preceptors to teach tonsillectomy in real time and to evaluate the condition of the postoperative wound in detail. We classified the postoperative state after tonsillectomy into three stages, based on the degree of residual subcapsular connective tissue. We assessed the association between the amount of residual subcapsular connective tissue and the underlying disease that required indication for tonsillectomy, the postoperative course, and the operation time in 33 patients who had undergone palatine tonsillectomy at our institution between May 2017 and November 2020. We found that the more the subcapsular connective tissue that remained, the less the postoperative pain and bleeding. This association suggests that conserving the subcapsular connective tissue is important. Bringing the endoscope closer to the surgical field to observe the field without blind areas enables adequate hemostasis and easy sharing of the surgical field; therefore, this method is also effective for teaching tonsillectomy to surgical trainees.
Keywords: confirmation of hemostasis; endoscopy; palatine tonsillectomy; teaching of surgery